Propagation Methods of Fragaria spp. in South America with Emphasis on Stolon Propagation: A Review - Angarita-Cacheo, Paula Alejandra; Cepeda-Palacios, Andrea Yasmith; Sánchez-Corredor, Natalie Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2023)
In the main South America countries, such as Argentina, Chile and Colombia, strawberry production exceeds 50,000 tons. Given the high demand for strawberry consumption, it is crucial to guarantee and optimize the efficiency of its propagation; however, the necessary information is not available to achieve this objective, therefore, it is essential to carry out a bibliographic review of the different methods of propagation of the species. For this purpose, a systematic review of scientific articles was conducted, using databases such as Scielo, ScienceDirect and Redalyc. Grey literature and technical data sheets without date restrictions were also consulted. The various documents consulted state that Fragaria spp. is a fruit that is highly valued throughout the world for its aroma, color, texture and, above all, for its nutritional components, including nutraceutical and antioxidant compounds that contribute to human health by reducing the risk of degenerative diseases, particularly cancer; in turn, it brings economic benefits in strawberry producing countries because it is a product marketed both fresh and processed for different markets. For the above mentioned, it is important to investigate and describe the different methods of propagation (sexual and asexual), emphasizing the asexual production by stolons, being this one of the techniques with superior benefits since it is a natural physiological process in the plant, which reduces production costs.